Preliminary Phytochemical Screening and GC-MS Analysis of Ethanolic Stem Extract of the Ethnomedicinal Plant- Tinospora crispa (L.) Miers [Menispermaceae] - Shree, J Akila; Krishnaveni, C (Asian Journal of Biological and Life Sciences)
Tinospora crispa (L.) Miers belongs to the family Menispermaceae and is used as a traditional medicine in China, Malaysia, Philippines, etc. It is one of the most popular local medicinal plants. It is also called Makabühai, which means “to give life”. The GCMS analysis revealed the presence of 20 compounds in the stem extract of Tinospora crispa. Some of the compounds are 1,2,3-Propanetriol, diacetate (CAS) Diacetin, 3-Tetradecene, (Z)- (CAS), 4-Penten-1-ol, trimethylsilyl ether, Diethyl Phthalate 1,2-benzene dicarboxylic acid, diethyl ester, 9-Eicosene, (E)- (CAS), Benzyl Benzoate, 9-Octadecenoic acid (Z)- (CAS) Oleic acid, Phosphonic acid, dioctadecyl ester (CAS) Di(n-octadecyl) phosphite, 9,12-Octadecadienoic acid (Z,Z)-, 9,12,15-Octadecatrienoic acid, (Z,Z,Z)-(CAS) Linolenic acid, 3-furylmethanol, 1,2-Benzenedicarboxylic acid, bis(2-ethylhexyl) ester (CAS) Bis(2-ethylhexyl) phthalate. This plant contains compounds such as alkaloids, saponins, glycosides, tannins, and flavonoids. These compounds have antipyretic, antiparasitic, antifungal, antidiabetic and antitumor properties.
Keywords: Ethanolic stem extract; Ethnomedicinal plant; Gc-Ms analysis; Medicinal compounds; Phytoconstituents; Tinospora crispa